2016
DOI: 10.5604/12321966.1203899
|View full text |Cite
|
Sign up to set email alerts
|

Level and conditioning of knowledge about breast cancer displayed by women in perimenopausal age

Abstract: Introduction. Women aged 50-69 are the most likely to develop breast cancer. Knowledge about breast tumours as well as regular examination are two of the key factors which reduce the risk of the disease, and increase both the success of treatment and chances of survival. Objective. The aim of the paper was to assess knowledge about risk factors, symptoms, screening, early diagnosis and breast cancer treatment among women in perimenopausal age. Materials and method. 400 women aged 45-60, residing in the Lublin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 10 publications
2
8
0
Order By: Relevance
“…In the papers of Shadbolt et al, the necessity of education, especially among teenagers, is expressed by as many as 89% of the surveyed women, while any health-promoting actions should be directed towards sources preferred especially by young women: schools (40%), the Internet (22%) and magazines (13%). Through education, the participants in the studies would like to learn about the symptoms, risk factors and treatment of the disease, similarly to the respondents from our research 32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the papers of Shadbolt et al, the necessity of education, especially among teenagers, is expressed by as many as 89% of the surveyed women, while any health-promoting actions should be directed towards sources preferred especially by young women: schools (40%), the Internet (22%) and magazines (13%). Through education, the participants in the studies would like to learn about the symptoms, risk factors and treatment of the disease, similarly to the respondents from our research 32 .…”
Section: Discussionmentioning
confidence: 99%
“…All over the world, actions are taken in order to build social awareness of endometriosis by various social campaigns and actions of the associations of sick women 32 . Since 2014, worldwide EndoMarches have been organised in March, the month of building this awareness, uniting over 60 countries in the world under one common objective: to eliminate the taboo and replace it with dialogue 29 .…”
Section: Introductionmentioning
confidence: 99%
“…The authors found significant difference between education level and the knowledge level. 9 In a cross-sectional study from Pakistan, Ahmed et al investigated knowledge level in nurses working at training hospitals at Karachi distinct. Authors found that knowledge level was high in 35% of subjects and these had a higher educational level than other subjects included.…”
Section: Discussionmentioning
confidence: 99%
“…In a Turkish study on 1342 women aged 18 Vast majority of participants were aware of the negligence while most participants were unaware that these methods should be employed for early diagnosis before the onset of symptoms. Similarly, in a study on female healthcare providers, Nilaweera et al investigated knowledge level and attitudes about breast and cervix cancer.¹ 9 Based on these data, it is apparent that the knowledge level in healthcare providers is sufficient by school education and in-service pieces of training but there are failures in behaviors and attitudes towards use of knowledge in real-life conditions. This may be due to place emphasis on the above-mentioned diseases and an insufficient level of awareness.…”
Section: Discussionmentioning
confidence: 99%
“…Results of research indicate that both the level of women's knowledge about breast cancer prevention and pro-health attitudes in this respect are insufficient in Poland (Bogusz et al, 2016). As breast cancer risk factors women most often list non-modifiable factors, e.g.…”
Section: Introductionmentioning
confidence: 99%